ANALISIS PENERAPAN STANDAR OPERASIONAL PROSEDUR PADA CUSTOMER SERVICE DI PT. BANK SUMUT CABANG SYARIAH MEDAN - Rangkuti, Sanna; Aidil, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Standard operational procedures are a device that regulates the stages of a work process or certain work processes. These work procedures are carried out based on written documents which are referred to as standard operating procedures (SOP). The purpose of this SOP is to explain the details or fixed standards regarding the work activities carried out. Repeatedly held within an organization or company. This research is motivated by the current competition between financial institutions, especially between banks, so PT. Bank Sumut Medan Syariah Branch uses a customer service strategy in order to make customers interested in using the services of the financial institution PT. Bank Sumut Medan Sharia Branch, this is implemented by customer service in order to provide good service to all customers, service is divided into two, namely new and existing customers. The focus of this research is on three things, namely, 1). What are the standard operating procedures (SOP) at PT. Bank Sumut Medan Sharia Branch?, 2) How do standard operating procedures (SOP) apply to PT Customer Service. Bank Sumut Syariah Medan?, 3). What are the results of implementing standard operating procedures (SOP) at PT. Bank Sumut Medan Sharia Branch?. This research uses a qualitative method with a case study type of research. The data sources used are primary data and secondary data. Data collection methods using observation, interviews and documentation methods. Based on the results of research conducted at PT. Bank Sumut Padangsidempuan Sharia Branch, services provided by PT. Bank Sumut Padangsidempuan Syariah Branch is more or less the same as the general service standards of fulfillment, guarantee, reliability, empathetic responsiveness, excellent service used. By PT. Bank Sumut Padangsidempuan Syariah Branch uses services in accordance with the SOP service standards that have been published by the company which are always updated so that the SOP used is always relevant. This SOP emphasizes excellent service in two things, namely appearance and attitude.